2016
DOI: 10.3998/ark.5550190.p009.495
|View full text |Cite
|
Sign up to set email alerts
|

An efficient access to novel 2H-pyrazino[2,1-b]quinazoline-1,6-diones via intramolecular alkyne hydroamination

Abstract: Starting from 3-propargylquinazolin-4(3H)-ones bearing a primary or secondary carboxamide group at position 2, an intramolecular alkyne hydroamination reaction, catalyzed by mercury(II) acetate, afforded 2H-pyrazino[2,1-b]quinazoline-1,6-diones in a two-step process that involves a rearrangement of the primary cyclization products. The title compounds represent a novel type of tricyclic heteroaromatic scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Mercury-catalyzed reactions were also well known for the formation of various complex scaffolds like tricyclic pyrazinones from the corresponding starting materials. For example, Zhang et al showed that refluxing anilide 177 in presence of a catalytic amount of Hg(OAc) 2 and 90% formic acid gave the tricyclic heterocyclic scaffold 178 [ 113 ]. It involved a two-step process with the rearrangement of the primary cyclization products ( Scheme 53 ).…”
Section: Reviewmentioning
confidence: 99%
“…Mercury-catalyzed reactions were also well known for the formation of various complex scaffolds like tricyclic pyrazinones from the corresponding starting materials. For example, Zhang et al showed that refluxing anilide 177 in presence of a catalytic amount of Hg(OAc) 2 and 90% formic acid gave the tricyclic heterocyclic scaffold 178 [ 113 ]. It involved a two-step process with the rearrangement of the primary cyclization products ( Scheme 53 ).…”
Section: Reviewmentioning
confidence: 99%
“…Conventional approaches (Figure ) to access pyrazin-1­(2 H )-ones mainly rely on intramolecular cyclization of amides with N -propargyl amines . However, most of these methods proceed in low yields and a limited broader substrate scope, resulting from the use of strong basic conditions, expensive catalysts, and toxic metals. , In light of this and due to the demand for producing novel heterocyclic building blocks, most of the conventional methods leave space for improvement. Propargyl amines are involved in different cycloisomerization reactions, particularly base-promoted exo or endo cyclizations.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, tricyclic heteroaromatic skeletons are very important moieties that are widespread in a large family of natural products with a broad range of attractive bioactivities. 1 Luotonin A (Figure 1) and derivatives, which possess a novel kind of tricyclic heteroaromatic scaffold, have displayed important biological activities such as anticancer, cytotoxic, and antiproliferative activity. 2,3 Because of this wide scope of biological activities, a great deal of study toward the synthesis and antifungal activities of luotonin A has been reported.…”
mentioning
confidence: 99%